Tannic acid-iron nanomaterial enhances rice growth and antioxidant defense under salt stress - Xiang Cheng (Frontiers in Plant Science)
Salinity stress severely impacts plant growth by reducing water uptake and biomass accumulation, while nanomaterial applications have emerged as effective solutions. This study introduces tannic acid-iron nanomaterial (TA-Fe Nanomaterial), a biocompatible nanomaterial synthesized via self-assembly, as a novel solution to mitigate salt stress. Characterized by lamellar morphology (200 nm average size) and robust thermal stability, TA-Fe Nanomaterial demonstrated potent reactive oxygen species (ROS) scavenging capabilities. Under 100 mM NaCl stress, applying 25 μ g/mL TA-Fe Nanomaterial enhanced rice seed germination, increasing root length by 85% compared to salt-stressed controls. In the hydroponic experiment, treated seedlings exhibited 70% and 87% increases in underground and aboveground lengths, alongside 133% higher fresh weight. Soil-cultivated rice showed 43–88% improvements in biomass and 67% greater shoot length. Furthermore, applying TA-Fe Nanomaterial can alleviate the aberrant ROS accumulation in leaves under the conditions of salinity stress. These findings suggest that TA-Fe Nanomaterial could be a promising tool for enhancing rice tolerance to salt stress, paving the way for future applications in sustainable agriculture.